2015
DOI: 10.1136/bcr-2015-210717
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cystic eye with optic nerve

Abstract: Congenital cystic eye (CCE) is a rare condition caused by failure of invagination of the optic vesicle resulting in a persistent cyst replacing the eye. An associated optic nerve attached to the cyst is a rarely reported phenomenon that has been sparsely described histologically, with no immunohistochemistry reported previously. The authors present a case of CCE with optic nerve tissue inserting into the cyst, and present the histological and immunohistochemical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Whereas all our cases were females and ipsilateral corneas were smaller by 2mm. Holland et al, 3 also reported an optic nerve cyst but unlike the current series, it was associated with a cystic eye ball. Shankar et al, reported bilateral retrobulbar cyst with associated optic disc colobomas.…”
Section: Discussioncontrasting
confidence: 55%
“…Whereas all our cases were females and ipsilateral corneas were smaller by 2mm. Holland et al, 3 also reported an optic nerve cyst but unlike the current series, it was associated with a cystic eye ball. Shankar et al, reported bilateral retrobulbar cyst with associated optic disc colobomas.…”
Section: Discussioncontrasting
confidence: 55%
“…The optic nerve was not identified in this study. Holland et al removed the cyst in a case of the congenital cystic eyeball and replaced it with a bioceramic implant [ 12 ]. Our case, an early teenage girl, underwent excision of the orbital cyst with an orbital implant and conformer by an oculofacial plastic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of CCE are remarkably rare. To date, only 52 cases of congenital cystic eyeball have been reported in the literature [ 5 – 12 ]. We discuss a case of a congenital cystic eyeball in a 14-year female and also describe the clinical features, diagnostic tools, differentials, and the management approach for such cases through an extensive literature review.…”
Section: Introductionmentioning
confidence: 99%